Os efeitos do financiamento do BNDES sobre o lucro e o crescimento das empresas - Gonçalves, Mariana Jesus Lourenço (2013)
In this paper the concepts of strategy and public p olicies related to the participation of BNDES in the Brazilian industrial scenario are presented and discussed. The expressiveness of BNDES’s acting, the origin of its resources and the relevance of its disbursements ratify the importance of its fina ncings for the Brazilian economy. The proposal of this research is to identify the ef fects of BNDES’s financing on the performance of the national industry companies, having as a target the understanding of how and to whom the financing of t he Bank generates value. At this point, this essay presents an evolutionary analysis of the concept of development bank and contextualizes BNDES’s activity in the Brazilia n reality, which is marked by the restriction to the long term credit, as a bank of d evelopment oriented to credit democratization, conciliating the idea of profitabi lity with the need to promote social objectives (BRUCK, 1998; BRUCK, 2009; HERMANN, 2010 ; CULPEPER, 2012). As a public institution, the Bank plays a unique ro le in the national economy, which makes it different from the traditional finan cial institutions. The effects of the financings should promote the conciliation of the p rivate benefits with the public priorities aimed by the institution. The fulfillmen t of these goals involves the concepts of value creation and the appropriation of the crea ted value. BNDES creates value when it democratizes the access to the credit to finance projects which are not attractive to private financial institutions. On the other hand, the appropriation of the value of the financial activity of BNDES is reflected on the met rics of the growth of the supported companies. The research result consolidated an analysis of per formance of the supported companies and allowed us to get to the conclusion t hat there are no evidences that after the support of the Bank, variations in the growth a nd profitability rates of these companies have taken place. Regarding 'BNDES Automá tico' ('BNDES Direct'), there was a positive and significant effect on the growth of some indicators.